Determination of Airborne Release Fractions from Solid Surrogate Nuclear Waste Fires. (2nd January 2022) - Hubbard, Joshua A.; Boyle, Timothy J.; Zepper, Ethan T.; Brown, Alexander; Settecerri, Taylor; Santarpia, Joshua L.; Bell, Nelson; Zigmond, Joseph A.; Storch, Steven S.; Maes, Brenda J.; Zayas, Nicole D.; Wiemann, Dora K.; et al.
Abstract: Solid waste samples consisting of shredded cellulose, coated with either mesoparticles of metallic salts or dried metal nitrate (lutetium, ytterbium, or depleted uranium) solutions, were generated to mimic solid nuclear waste. After burning these samples, the masses of the aerosolized metal cations were quantified by leaching them from air filters and analyzing the leachate with inductively coupled plasma mass spectrometry. The airborne release fractions (ARFs) for Lu and depleted uranium nitrates were 1 × 10 −4, and 3 × 10 −3 for Lu and depleted uranium mesoparticle salts, respectively. Uncertainties in ARFs were approximately 10% for the metal nitrates and 30% for the metallic mesoparticles. These data are most applicable to waste materials with 1% metal mass loading where the initial respirable fraction of contaminant particles is one. ARFs were consistent across the two metals, but there was an order of magnitude difference with respect to the physical and chemical form (mesoparticle salt versus nitrate). Cellulose combustion literature indicates that combustion pathways were likely affected by off-gassing and endothermic decomposition reactions. In comparison to ARF values from DOE-HDBK-3010-94, "Airborne Release Fractions/Rates and Respirable Fractions for Nonreactor Nuclear Facilities, " this dataset was consistent with previous results but provides a well-characterized and reproducible method for doping cellulosic materials with nuclear waste surrogates to serve as a baseline for future experimental and computational works.